Peningkatan Taraf Perekonomian Masyarakat di Desa Trasan Melalui Pelatihan dan pendampingan Usaha Peternakan Ayam Unggul - Khairul Ikhwan; Ipuk Widayanti; Dian Marlina Verawati; Sofyan Ashari Nur (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
IMPROVING THE ECONOMIC LEVEL OF THE COMMUNITY IN TRASAN VILLAGE THROUGH TRAINING AND MENTORING FOR SUPERIOR CHICKEN FARMING BUSINESSES: Trasan Village, Bandongan District, Magelang Regency, faces significant economic challenges, particularly the high unemployment rate (18.29% in 2022). Low levels of education and dependence on the agricultural sector and small businesses lead to unstable incomes. One economic potential that has not been optimized is free-range chicken farming, which is still managed traditionally without financial records, modern cultivation techniques, or broad market access. This community service program aims to improve community welfare through training and mentoring for superior free-range chicken farming-based entrepreneurship. The main target is the productive age group who do not have permanent jobs. This program will provide education related to business management, efficient cultivation techniques, and broader and modern marketing strategies. The approach used includes simple financial management training, improving skills in raising free-range chickens, and facilitating marketing through digital media and partnerships with traditional markets and restaurants. The expected outputs of this program include publication of the results of the community service in the Abdipraja journal, articles in the online media Magelang Ekspres, and Intellectual Property Rights (IPR) certificates related to innovations in free-range chicken farming management. This program is expected to create sustainable businesses, reduce unemployment, and strengthen the local economy in an inclusive and sustainable manner.